Implementation of Virtual Execution Environments for improving SLA-compliant Job Migration in Grids - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Workshop on Scheduling and Resource Management for Parallel and Distributed Systems)
Abstract: Commercial Grid users demand for contractually fixed QoS levels. Service Level Agreements (SLAs) are powerful instruments for describing such contracts. SLA-aware resource management is the foundation for realizing SLA contracts within the Grid. OpenCCS is such an SLA-aware RMS, using transparent checkpointing to cope with resource outages. It generates a compatibility profile for each checkpoint dataset, so that the job can be resumed even on resources within the Grid. However, only a small number of Grid resources comply to such a profile. This paper describes the concept of virtual execution environments and how they increase the number of potential migration targets.The paper also describes how these virtual execution environments have been implemented within the OpenCCS resource management system.

Europa und die Religionen - Krimphove, Dieter (Kirche & Recht, Zeitschrift für die kirchliche und staatliche Praxis)

Germany, Belgium, France, and Back Again: Job Migration using Globus - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Conf. on Grid Computing and Applications (GCA))

Diritto bancario europeo e tecniche del legislatore comunitario - Krimphove, Dieter (Contratto e impresa / Europea Pubblicazione semestrale)

Virtual Execution Environments for ensuring SLA-compliant Job Migration in Grids - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Conf. on Services Computing (SCC))
OpenCCS is an SLA-aware resource management system which uses transparent checkpointing of applications and migration of checkpoint datasets for ensuring SLA-compliance also in case of resource outages. Migration of checkpoints presumes a high grade of compatibility between source and target resource. Hence, even in large Grid systems only a small number of resources are eligible migration targets. This short paper describes the concept of virtual execution environments and how they increase the number of potential migration targets. It will also outline an implementation within OpenCCS.

Job Migration and Fault Tolerance in SLA-aware Resource Management Systems - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Conf. on Grid and Pervasive Computing (GPC))
Contractually fixed service quality levels are mandatory prerequisites for attracting the commercial user to Grid environments. Service Level Agreements (SLAs) are powerful instruments for describing obligations and expectations in such a business relationship. At the level of local resource management systems, checkpointing and restart is an important instrument for realizing fault tolerance and SLA awareness. This paper highlights the concepts of migrating such checkpoint datasets to achieve the goal of SLA compliant job execution.

Random Graphs for Peer-to-Peer Overlays - Schindelhauer, Christian; Mahlmann, Peter (The European Integrated Project "Dynamically Evolving, Large Scale Information Systems (DELIS), Proceedings of the Final Workshop)
Modern peer-to-peer networks consist of several network layers and distributed algorithms providing features like indexing, resource balancing, entry protocols, security, anonymity, and cryptography. Since peer-to-peer networks are highly dynamic, a fundamental task in the design of these networks is to provide high connectivity. We propose a solution by distributed random link exchange algorithms such that the overlay network can be a connected random graph or use a random graph as backbone. Random graphs are expander graphs have logarithmic diameter, high node connectivity, excellent communication properties, and are expander graphs with high probability. In summary: they are an excellent choice to improve the stability and robustness of a dynamic network.

Detours Save Energy in Mobile Wireless Networks - Ooi, Chia Ching; Schindelhauer, Christian (MWCN'08: Proc. of IFIP Joint Conference on Mobile Wireless Communications Networks (MWCN 2008) and Personal Wireless Communications (PWC 2008))
Autonomous robotic systems have been gaining the attention of research community in mobile ad hoc network since the past few years. While motion cost and communications cost constitute the primary energy consumers, each of them is investigated independently. By taking into account the power consumption of both entities, the overall energy efficiency of a system can be further improved. In this paper, the energy optimization problem of radio communication and motion is examined. We consider a hybrid wireless network that consists of a single autonomous mobile node and multiple relay nodes. The mobile node interacts with the relays within its vicinity by continuously communicating high-bandwidth data, e.g. triggered by a multimedia application like video surveillance. The goal is to find the best path such that the energy consumption for both mobility and communications is minimized. We introduce the Radio-Energy-Aware (REA) path computation strategy by utilizing node mobility. Given the starting point, the target point and the position of the relays, our simulation results show that the proposed strategy improves the energy efficiency of mobile node compared to the Motion-Energy-Aware (MEA) path constructed based only on the mobility cost.

Enhancing SLA Provisioning by Utilizing Profit-Oriented Fault Tolerance - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Conf. on Parallel and Distributed Computing and Systems (PDCS))

Energy-Efficient Distributed Target Tracking Using Wireless Relay Robots - Ooi, Chia Ching; Schindelhauer, Christian (ARS'08: Proc. of the 9th International Symposium on Distributed Autonomous Robotic Systems (DARS 2008))

Increasing Fault-tolerance by Introducing Virtual Execution Environments. - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin

Paderborn, Belgien, Frankreich und zurück - Hovestadt, Matthias; Keller, Axel; Voss, Kerstin (Paderborner Universitätszeitschrift (puz))

Europäische Bildung im Sachunterricht – Bilanz und Perspektiven für Forschung und Praxis. Vortrag an der 17. Jahrestagung Kommission „Grundschulforschung und Pädagogik der Primarstufe“ der Deutschen Gesellschaft für Erziehungswissenschaft. Bergische Universität Wuppertal - Büker, Petra
September 2008

Biografische Arbeit in der LehrerInnenausbildung. Fritz Seydels Konzept einer Verknüpfung ästhetischer und biografischer Verfahren. Vortrag im Forschungskolleg „Ästhetisches Lernen“ am PLAZ. Universität Paderborn - Büker, Petra; Nitsche, Angelika
Februar 2008

Lokale Strategien zur Optimierung von Kommunikationsketten - Pietrzyk, Peter

Space-Time Continuous Models of Swarm Robotic Systems - Hamann, Heiko

Was bedingt die Wahl eines nicht empfohlenen höheren Bildungsgangs? Zeitschrift für Erziehungswissenschaft, 11, 626-647 - Bloh, Bea; van Ophuysen, Stefanie (Zeitschrift für Erziehungswissenschaft)

Challenges and opportunities for methodologically principled L2 pronunciation training in German textbooks and class - Müller, Mareike (Forum Deutsch – Research Forum)
The teaching of pronunciation in foreign language classes has experienced methodological waves of interest over the last century. Regarded as an insignificant part of language learning in the grammar translation approach, the teaching of pronunciation “grew in prominence with the rise of the Direct Method and Audiolingualism, only to be pushed again to the sidelines with the ascendancy of Communicative Language Teaching … and the Natural Approach” (Jones, 2005, p. 178). Although phonetics has drawn more attention within the context of second language (L2) acquisition since the late 1980s, shortcomings inhibiting the teaching and learning of L2 pronunciation are still apparent, particularly within the realm of German as a Foreign Language (GFL), where a lack of appropriate pronunciation training and training material is observable (Dieling & Hirschfeld, 2000).

The European Integrated Project "Dynamically Evolving, Large Scale Information Systems (DELIS)", Proceedings of the Final Workshop, Barcelona, February 27-28, 2008 - Meyer auf der Heide, Friedhelm

Self-optimizing Mechatronic Systems: Design the Future - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm